The Academic Writing Skills Programme: A model for technology-enhanced, blended delivery of an academic writing programme - Boyle, Jennifer; Ramsay, Scott; Struan, Andrew (Journal of University Teaching and Learning Practice, 2019)
Recognising the varied challenges presented by an increasingly diverse student body at our UK university (a research-intensive institution with a high proportion of international and widening participation students), an online and blended writing programme was developed. The Academic Writing Skills Programme (AWSP) is a fully online, compulsory writing diagnostic, consisting of a range of multiple-choice questions on grammar and a short essay. Run centrally by a department of multidisciplinary academic writing advisers, the programme was taken from a small, discipline-specific writing programme and transformed into an institution-wide, fully-funded technology-enhanced academic language course. This paper details and evaluates the process through which this development was achieved; it discusses the challenges encountered, explores the pedagogical justification and background of our approach, provides student assessment and feedback on the impact and efficacy of the programme, and offers guidance for practitioners in academic language support.